Impacto da adoção da IFRS 9 nos indicadores econômico-financeiros dos principais bancos no Brasil - Oliveira, Fabio Bassi de (2020)
In view of the expectation for the adoption by the Brazilian Central Bank of the international accounting standard IFRS 9 - Financial Instruments, this research purposes to verify, for the main Brazilian banks, whether the economic and financial indicators obtained from the financial statements prepared under the new IFRS 9 requirements improved when compared to the indicators under the Brazilian Central Bank standards (Cosif). It was considered as an improvement on an indicator only when the mean score of this indicator under the IFRS standard resulted in an enhanced indicator when compared to the mean score of the indicator obtained under Cosif standards and if the result of the Wilcoxon’s Sign test is statistically relevant for a 5% significance level. A descriptive and empirical-analytical research was carried out, considering as the primary source of data the financial statements disclosed by nine of the main banks in Brazil, in both accounting standards. The result of the Wilcoxon’s Sign nonparametric test is statistically significant and indicated improvement, in the IFRS view, for three of the six analysed indicators, specifically Financial Independence, Credit Participation and Leverage, as the Equity and Credit Operations lines where identified as the main causes these variations.